2015
DOI: 10.5603/fhc.a2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

High motility group box 1 (HMGB1) protein and its receptor for advanced glycation end products (RAGE) expression in chronic rhinosinusitis without nasal polyps

Abstract: Introduction. Chronic rhinosinusitis (CRS) affects 14% of the world population. The high motility group box 1 (HMGB1) protein triggers inflammation, cell proliferation and cell survival through its receptor for advanced glycation end products (RAGE) upon release from stressed or necrotic cells. The aim of the study was to analyze the expression and function of HMGB1 and RAGE in CRS, providing more information about HMGB1 signaling pathway in CRS, to determine its potential clinical significance. Material and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…In turn, autoantibodies directed against nucleosomes and double-stranded DNA are characteristics for SLE. Our previous study demonstrated the expression of RAGE and HMGB1 in epithelial cells of sinonasal mucosa samples obtained from patients with chronic rhinosinusitis or in epithelial cells of middle ear cholesteatoma [12,22]. We observed a strong correlation between the disease severity and RAGE expression.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In turn, autoantibodies directed against nucleosomes and double-stranded DNA are characteristics for SLE. Our previous study demonstrated the expression of RAGE and HMGB1 in epithelial cells of sinonasal mucosa samples obtained from patients with chronic rhinosinusitis or in epithelial cells of middle ear cholesteatoma [12,22]. We observed a strong correlation between the disease severity and RAGE expression.…”
Section: Discussionsupporting
confidence: 50%
“…Paraffin sections of GO patients and NC patients were immunostained using NovoLink Polymer Detection Systems (Novocastra Laboratories, Newcastle, UK) and the following primary antibodies diluted 1 : 100 in Antibody Diluent (Dako): rabbit polyclonal anti-human HMGB1 (LS-C2691, LifeSpan BioSciences, Inc., Seattle, WA, USA) and mouse monoclonal anti-human RAGE (LS-B6042, LifeSpan BioSciences, Inc., Seattle, WA, USA). Deparaffinated and rehydrated sections were stained according to the manufacturer's instructions, as previously described [12]. The activity of endogenous peroxidase was blocked by Peroxidase Block (NovoLink Polymer Detection System; Novocastra Laboratories).…”
Section: Patients and Tissuementioning
confidence: 99%
“…In total, 21 articles related to HMGB1 expression in upper airways inflammation and the effects of its blockage by inhibitors in clinical trials have been selected for our review. 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 The search results are summarized in Table 1 .…”
Section: Review Of Literaturementioning
confidence: 99%
“…HMGB1 closely contributes to chronic rhinosinusitis with or without nasal polyps [39,40]. Furthermore, HMGB1 disrupts the airway epithelial barrier of human bronchial and lung epithelia via angulin-1/LSR [31,41].…”
Section: Hmgb1 Decreases Angulin-1/lsr Expression and Epithelial Barrier Function In Hnecsmentioning
confidence: 99%